Organs at risk's tolerance and dose limits for head and neck cancer re-irradiation: A literature review. (November 2019) - Dionisi, F.; Fiorica, F.; D'Angelo, E.; Maddalo, M.; Giacomelli, I.; Tornari, E.; Rosca, A.; Vigo, F.; Romanello, D.; Cianchetti, M.; Tommasino, F.; Massaccesi, M.; et al.
Highlights: We reviewed the clinical literature regarding head and neck cancer re-irradiation. We focused on radiation toxicity, organs at risk tolerance and dose limit recommendations. Data of 3766 patients from 39studies were analyzed. Grade ≥3 pooled acute and late toxicities were 32% and 29.3%, respectively. Treatment toxicity is impacted by interval time, fractionation and volumes. Dose limits were found and discussed for carotid arteries, temporal lobes, mandible. Abstract: Re-irradiation is becoming an established treatment option for recurrent or second primary head and neck cancer(HNC). However, acute and long-term RT-related toxicities could dramatically impact patients' quality of life. Due to the sparse literature regarding HNC re-irradiation, data on tolerance doses for various organs at risk (OARs) are scarce. Our aim was to systematically review the clinical literature regarding HNC re-irradiation, focusing on treatment toxicity, OARs tolerance, and dose limit recommendations. Thirty-nine studies (three randomized, five prospective, 31 retrospective) including 3766 patients were selected. The median interval time between the first course and re-irradiation was 28  months (range, 6–90). In 1043 (27.6%) patients, postoperative re-irradiation was performed. Re-irradiation doses ranged from 30 Gy in 3 fractions using stereotactic technique to 72 Gy in conventional fractionation using intensity-modulated radiotherapy. Pooled acute and late toxicityrates ≥G3 were 32% and 29.3%, respectively. The most common grade 3–4 toxic effects were radionecrosis, dysphagia requiring feeding tube placement and trismus. In 156 (4.1%) patients, carotid blowout was reported. Recommendations for limiting toxicity included the time interval between radiation treatments, the fractionation schedules, and the re-irradiation treatment volumes. Cumulative dose limit suggestions were found and discussed for the carotid arteries, temporal lobes, and mandible.